2003
DOI: 10.1161/01.cir.0000074209.17561.99
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Induction of Arteriogenesis in Hypoperfused Rat Brain Via Granulocyte-Macrophage Colony-Stimulating Factor

Abstract: Background-Colony-stimulating factors (CSFs) have been shown to effectively induce arteriogenesis in the hindlimb.Moreover, clinical trials demonstrated positive effects of CSFs on arteriogenesis in patients with coronary artery disease. However, patients with cerebrovascular disease have not yet profited from treatments aimed at the growth of brain vessels. Thus far, angiogenesis studies have failed to demonstrate improvement of stroke outcome. Arteriogenesis differs from angiogenesis in that it substitutes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
93
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 27 publications
7
93
2
1
Order By: Relevance
“…Some previous studies evaluated arteriogenic effects after longer time intervals-for example, after systemic administration of growth factorssuggesting a long-term recovery effect with the requirement of a longer time interval to permit sufficient structural remodeling. 4,5 Other studies, however, also demonstrated structural changes as soon as 1 week after conductance vessel occlusion 27,28 and recent findings from our group on vascular remodeling in a mouse model of chronic cerebral hypoperfusion are in line with these results. 19 Next to the structural remodeling, functional improvement of the vasodilation response could additionally contribute to the higher CVRC after treatment with e-EPC.…”
Section: Therapeutic Stimulation Of Collateral Vessel Growth In Chronsupporting
confidence: 67%
See 2 more Smart Citations
“…Some previous studies evaluated arteriogenic effects after longer time intervals-for example, after systemic administration of growth factorssuggesting a long-term recovery effect with the requirement of a longer time interval to permit sufficient structural remodeling. 4,5 Other studies, however, also demonstrated structural changes as soon as 1 week after conductance vessel occlusion 27,28 and recent findings from our group on vascular remodeling in a mouse model of chronic cerebral hypoperfusion are in line with these results. 19 Next to the structural remodeling, functional improvement of the vasodilation response could additionally contribute to the higher CVRC after treatment with e-EPC.…”
Section: Therapeutic Stimulation Of Collateral Vessel Growth In Chronsupporting
confidence: 67%
“…20 In the brain, therapeutic stimulation of collateral vessel growth at the level of the basal vasculature was initially reported by Buschmann et al and later confirmed by our group. 4,5 Overall, treatment with e-EPC but not e-EPDC compared favorably with these results and led to a significant increase of the ICA and MCA vessel diameters in the anterior circulation. This, together with the positive remodeling of the leptomeningeal and microcirculatory vasculature in e-EPCtreated animals (see below) could account for their improved CVRC and reduced need for compensational cross-flow via the P1 segment, which serves as the natural conduit between the anterior and posterior circulation.…”
Section: Therapeutic Stimulation Of Collateral Vessel Growth In Chronmentioning
confidence: 68%
See 1 more Smart Citation
“…The functional significance of brain arteriogenesis is reflected by an improvement of the hemodynamic reserve, as demonstrated by the gradual recovery of CO 2 reactivity, which, shortly after 3-VO, is completely suppressed (1). Under conditions of permanently increased vascular shear stress, arteriogenesis proceeds spontaneously, but the speed of vascular growth can be markedly accelerated by various cytokines, notably by GM-CSF (8).…”
Section: Discussionmentioning
confidence: 99%
“…In the 3-VO model, GM-CSF also markedly accelerated arteriogenesis, as reflected by the faster expansion of the diameter of the posterior cerebral artery and normalization of the hemodynamic reserve within 1 week after onset of treatment (8). GM-CSF-induced arteriogenesis may therefore protect the brain against stroke by improvement of collateral blood supply.…”
mentioning
confidence: 93%